INTRODUCTION TO LEE OU-FAN LEE'S "SOMES NOTES ON 'CULTURE', 'HUMANISM', AND THE 'HUMANITIES' IN MODERN CHINESE CULTURAL DISCOURSES" - Iser, Wolfgang (Surfaces, 1995)
In the context of the Second International Conference on Humanistic Discourse, this texte introduces Lee Ou-fan Lee's "Some Notes on 'Culture', 'Humanism', and 'Humanities' in Modern Chinese Cultural Discourses" and reports on the central concerns that emerged in its discussion.